2017
DOI: 10.1177/0162643417746149
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Video Modeling Interventions on the Independent Living Skills of Students With Autism Spectrum Disorder and Intellectual Disability

Abstract: iii Individuals with autism spectrum disorder (ASD) and intellectual disability (ID) often have independent living skill deficits. Video modeling (VM) may be one particularly effective intervention to improve skills in this area. However, the most effective and efficient variations have yet to be determined. The researcher conducted a search for studies investigating the effects of VM on the independent living skills of school-aged students with ASD and/or ID. Nineteen single-subject studies and 65 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
(172 reference statements)
1
12
0
1
Order By: Relevance
“…Such responses point to common misunderstandings of the VM intervention and further highlight the need for more training on the various ways of implementing VM. For example, (a) Van Laarhoven, Zurita, Johnson, Grider, and Grider (2009) and Wynkoop, Robertson, & Schwartz, (2018) found VM was effective in improving skills of students with IQ scores as low as 30. Also, (b) teachers do not always have to serve as models in VM; other adults, peers, and the target students themselves can serve as models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such responses point to common misunderstandings of the VM intervention and further highlight the need for more training on the various ways of implementing VM. For example, (a) Van Laarhoven, Zurita, Johnson, Grider, and Grider (2009) and Wynkoop, Robertson, & Schwartz, (2018) found VM was effective in improving skills of students with IQ scores as low as 30. Also, (b) teachers do not always have to serve as models in VM; other adults, peers, and the target students themselves can serve as models.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, very little is known regarding teacher beliefs about the intervention. The lead author recently conducted a thorough review of the literature including a key word search of three electronic databases: a review of all titles and abstracts when necessary (N ¼ 2,236), ancestral searches of key studies (n ¼ 10), a review of 12 pertinent literature reviews, and a hand search of four relevant journals (Wynkoop, Wissinger, & Van Horn, 2019). We did not identify any studies that directly address our research interests.…”
Section: Purpose and Research Questionsmentioning
confidence: 99%
“…Susilowati et al (2018) ing dressing skills among students with intellectual disabilities. Wynkoop et al (2017), moreover, investigated the impact of two video modeling interventions and a third non-video-based intervention on enabling four autistic and students with intellectual disabilities to practice their living skills, such as cleaning, preparing food, and laundering clothes independently. To this end, an adapted alternating treatment design was used to investigate the comparative impacts of video modeling, along with promoting and reinforcement, continuous video modeling, along with prompting and reinforcement, and prompting and reinforcement.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, the majority of people with multiple disabilities experience difficulties in performing daily living skills independently, such as cleaning, cooking, self-care, and managing personal finances, that hinder their ability to live without getting support from others (Bridges et al, 2019). To address this problem, several studies (Wynkoop et al, 2017;AL-Salahat, 2016) indicated that teaching independent life skills, such as cleaning, preparing food, laundering clothes, and preparing sandwiches, to students with multiple disabilities enhances their autonomy, self-reliance, and reduces some of the required time and effort for providing direct care for them.…”
Section: Introductionmentioning
confidence: 99%
“…Hal tersebut ditunjukkan karena adanya keterlambatan dalam melakukan aktivitas dibandingkan dengan anak normal. Selain itu, anak down syndrome memiliki hambatan dalam mengembangkan kemampuan mandiri dalam dirinya, hal ini sangat memprihatinkan karena jika anak tidak diberikan intervensi yang tepat maka dapat mengakibatkan anak memiliki sifat ketergantungan terhadap orang yang lebih dewasa (Wynkoop et al, 2017) Sehingga, hal tersebut yang menjadikan anak down syndrome lebih sulit untuk ditangani (Lee et al, 2019).…”
Section: Pendahuluanunclassified